The philosophical anthropological categories in the thought of Miguel De Unamuno - Castillo Gaitán, Bernardo Antonio (2023)
It is intended to explain that consciousness and death are two philosophical anthropological categories that are present in the thought of Miguel de Unamuno and these are expressions of the most human possible. For the development of the text, the document analysis methodology is used, which implies consulting, selecting and detecting the contents of the topic. It is concluded that death and consciousness are two categories that define the expressions and experiences of the human being and that Unamuno's philosophical anthropology has an individual character aimed at the explanation of the concrete human being, of flesh and blood.